Fabrication and characterisation of ceramic hollow fibre membrane from metakaolin and corn cob ash for oil–water separation - Kamarudin, Noor Hasliza (2022)
Oily wastewater discharged into the environment causes serious global water pollution issues, which necessitates emerging recovery technologies, such as membranes for water purification. In this study, ceramic hollow fibre membrane (CHFM) derived from abundant waste materials of metakaolin (MK) and corn cob ash (CCA) were successfully developed via phase inversion/sintering techniques. As weakness of MK membrane is always associated to the brittleness property that lead to the reduction of strength value. Thus, further improvement by substituting a proportion of CCA into MK acts as pore-forming material and assist sintering mechanism in the preparing MK–CCA CHFM. The fabrication of CHFM involves CCA-based CHFM (H-NCA), MK–non-treated CCA-based CHFM (H-MNCA), and MK–treated CCA-based CHFM (H-MTCA) with processing parameters of ceramic powder ratio and ceramic powder content, bore fluid flow rate, and sintering temperature. Unstable H-NCA and H-MNCA membranes were observed during dope preparation and membrane spinning, owing to corn cob ash–potassium chloride (CCA–KCl) dissolution, which is significance as a green viscosity enhancer and pore agent in H-MNCA based on the precursor and sintered membrane matrix structure. The optimum MK:NCA ratio at 75:25 generated mechanical strength of 41.61 MPa and permeate water flux (PWF) of ~1159.93 L/m2h. The final membrane preparation involved the TCA, produced the best H-MTCA asymmetric structure at MK–TCA of 45 wt%, bore fluid flow rate of 10 mL/min, and sintering temperature of 1150 °C. The performance tests showed a stable PWF (~266.52 L/m2h), enhanced mechanical strength (82.78 MPa), and high oil–water separation efficiency (93.06%). Hence, CCA offered efficient sintering additive, not only formed in-situ reaction of phase network but also allow sintering at lower temperature, which preserved the sustainability technology.